The influence of temperature and pressure on macro- and micro-mixing in compressed fluid flows; mixing of carbon dioxide and ethanol above their mixture critical pressure - Bassing, Daniel; Braeuer, Andreas Siegfried (Journal of Supercritical Fluids, 2021)
We report quantitative composition data on continuous jet-mixing of ethanol with ambient carbon-dioxide (CO2) at temperatures (T=[313 K–333 K]) and pressures (p=[9 MPa to 11 MPa]) in the vicinity of the mixture critical pressure of the binary system. Progress of mixing is quantified simultaneously on the macro- and on the micro-scale. The lag between mixing on both scales is quantified spatially resolved and in the jet-mixing region. We found that surprisingly mixing below the mixture critical pressure in the two-phase mixing regime can be more efficient than mixing above the mixture critical pressure in the single-phase mixing regime. Density was the key parameter influencing the mixing efficiency.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Composition; Critical pressure; Jet; Mixing; Mixing scale